2021
DOI: 10.31234/osf.io/s6eh3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The chemical induction of synaesthesia

Abstract: Objective Preliminary research suggests that experiences resembling synaesthesia are frequently reported under the influence of a diverse range of chemical substances although the incidence, chemical specificity, and characteristics of these effects are poorly understood. Methods Here we surveyed recreational drug users and self-reported developmental synaesthetes regarding their use of 28 psychoactive drugs comprising 12 different drug classes and whether they had experienced synaesthesia under the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
3
2
0
Order By: Relevance
“…Interestingly, our findings seem to indicate that LSD is more prone to evoke Audio-Visual Synesthesia compared to psilocybin, supporting previous reports that LSD is highly effective in inducing synesthesia [73,74]. In a survey among recreational psychedelic users, the highest incidence rate of drug-induced synesthesia was reported for LSD [75] and a study comparing the effects of LSD (1 μg/kg) and psilocybin (150 μg/kg) also found significantly more synesthesia in the LSD group [4]. Considering that LSD not only interacts with serotonin receptors, but also with dopaminergic and adrenergic receptors [76,77], our results could be interpreted in line with evidence that drug-induced synesthesia is not exclusively a result of serotonergic activation [75].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Interestingly, our findings seem to indicate that LSD is more prone to evoke Audio-Visual Synesthesia compared to psilocybin, supporting previous reports that LSD is highly effective in inducing synesthesia [73,74]. In a survey among recreational psychedelic users, the highest incidence rate of drug-induced synesthesia was reported for LSD [75] and a study comparing the effects of LSD (1 μg/kg) and psilocybin (150 μg/kg) also found significantly more synesthesia in the LSD group [4]. Considering that LSD not only interacts with serotonin receptors, but also with dopaminergic and adrenergic receptors [76,77], our results could be interpreted in line with evidence that drug-induced synesthesia is not exclusively a result of serotonergic activation [75].…”
Section: Discussionsupporting
confidence: 87%
“…Considering that LSD not only interacts with serotonin receptors, but also with dopaminergic and adrenergic receptors [76,77], our results could be interpreted in line with evidence that drug-induced synesthesia is not exclusively a result of serotonergic activation [75]. LSD's pronounced modulation of Audio-Visual Synesthesia via non-5-HT2A mechanism of action may be associated with the etiology of the rarely occurring hallucinogen-persistent perception disorder (HPPD).…”
Section: Influences On Subjective Experiencessupporting
confidence: 80%
See 2 more Smart Citations
“…While synaesthesia of some description was shared by many subjects (common to tryptamine psychedelics, especially LSD, and typically sound color, Luke et al, 2022 ), one individual, ST , depicted an elaborate multisensory-cognitive manifestation. Psychedelic synaesthesia may be prompted by the global hyperconnectivity of non-local networks, which is concomitant with the disintegration of the DMN, which facilitates ego consciousness.…”
Section: Discussionmentioning
confidence: 99%